Risk of malnutrition assessment in hospitalised adults: A scoping review of existing instruments - Chrástecká, Marie; Blanař, Vít; Pospíchal, Jan (Journal of clinical nursing, 2023)
AIMS AND OBJECTIVES: The aim of this study was to find tools for screening the risk of malnutrition in adult hospitalised patients, evaluate their key characteristics including selected psychometric properties and propose the most appropriate tools for nursing practice. BACKGROUND: A large number of existing tools for nutritional screening make it difficult to be aware of all the possibilities and especially to select the optimal tool. DESIGN: The research methodology was designed as secondary research using a scoping review search to map and compare existing tools for assessing the risk of malnutrition in hospitalised adults. METHODS: The analysis focused on the selected psychometric properties of the instruments (sensitivity, specificity, positive and negative predictive value) and key characteristics relevant to the selection of an appropriate instrument. This study follows the PRISMA-ScR Checklist. RESULTS: The review included 27 publications containing 17 tools. The best sensitivity (57%-100%) and specificity (76%-96%) were achieved by the Malnutrition Universal Screening Tool (MUST) and the Nutritional Risk Screening 2002 (NRS 2002). Minimal Eating Observation and Nutrition Form-Version II (MEONF-II) has solid sensitivity (up to 73%), specificity (88%) and high positive predictive values (81%-82%). CONCLUSIONS: The MUST, NRS 2002 and MEONF-II showed satisfactory psychometric properties. MEONF-II and MUST are able to assess risk without weighing the patient. The Hand Grip Strength (HGS) assessment can be recommended to detect reductions in muscle strength. RELEVANCE TO CLINICAL PRACTICE: We recommend the MUST, NRS 2002 and MEONF-II tools for use in clinical practice, as they have the best psychometric properties and are user-friendly. The HGS, which proved to be related to the length of hospital stay (LOS) and used as an indicator of protein-energy malnutrition in obese patients, may be a useful complementary tool. For nursing practice, we recommend selecting a tool with respect to the specifics of a particular workplace.
Keywords: Malnutrition; Nutritional Status; Hand Strength; podvýživa; dospělí; síla ruky; nutriční stav; Adult; hodnocení stavu výživy; Humans; Risk Assessment; lidé; Length of Stay; délka pobytu; hodnocení rizik; Nutrition Assessment